Online Education in the Indian Pharmaceutical Industry: Assessing Its Acceptance and Impact on Employers During Hiring and Promotion Decisions - Sinha, Jyotsana (Digital Repository of Theses, 2026)
Pharmaceutical industry plays a crucial in advancing and developing new drugs, innovative treatments, digital technologies and medical facilities for the welfare of lives globally. The worldwide revenue of drugs market reached 1.48 trillion U.S. dollars in 2022 (Statista, 2023) and provided direct employment to over 5.5 million highly productive persons in 2017 (Ostwald, et al., 2020). India has emerged as a global leader in the pharmaceutical industry, with factors such as cost-effective manufacturing, a skilled workforce, digital advancements, and robust marketing and distribution systems. Indian government initiatives like Make in India, Digital India, and Production Link Initiatives (PLI) have strengthened India’s drug industry ecosystem at global level. Despite these advancements, the industry is facing skill shortages, particularly in digital technologies. NASSCOM (2022) reports a 21.1% demand-supply gap in Tech Talent, which is expected to increase to 1.4M-1.8M by 2026, specifically in areas such as AI/ML, cloud-based technology, and cybersecurity. The demand for skilled labors in healthcare, cyber security, digital technologies, data engineering, clinical, industrial and economic research, and genomic and phenotypic analytics is more than the supply (ABPI, 2022; Diaz-Infante, Lazar, Ram, & Ray, 2022) leading to effective implementation of Pharma 4.0. These challenges are compounded by high attrition rates and difficulty in retaining skilled employees (Roy & Devi, 2016). Online education presents a promising solution, offering flexible and tailored learning opportunities. This paradigm shift towards online education provides a viable solution to address the evolving demands of pharmaceutical industry along with a promising approach to address workforce challenges, and bridging skill gaps within this sector. However, research analyzing the employer’s perception of candidates with online diploma / degree / certification and their employability is limited to few geographies, specific fields, and industries. Study on employability of students with online education (Diploma / Degree / Certification) in pharmacy sector in India is either absent or rare. This highlights the importance of further research in this specific industry, highlighting potential opportunities and challenges unique to pharmaceutical education and employment. This research aims to explore the perspective of employers of Pharmaceutical Industry in India towards their hiring and promotion decisions about candidates with online education / diploma /degree/ certification (graduate, post-graduate, and doctoral). This study tries to find out if the online education is being recognized and accepted by the pharmaceutical employers in India.